Aplication of Controlled FACTS an Effective Way to Increase Stability and Optimize Voltage Levels in the Power System - Balametov , A.B. (Herald of Azerbaijan Engineering Academy, 2023)
The article discusses the use of managed FACTS to solve the problem of voltage stability of the power system and the application of optimization methods for the optimal location, installed power of devices and minimization of losses. To increase the static stability of the Azerbaijan EES, it is proposed to improve the damping of low-frequency oscillations by placing a unified regulator of power flows in the power system.